What to Do about Taste-less Transmissions? Useful Television Histories - Hughes, Kit (Unlocking Television Archives in the Digital Era. 16th Media Mutations International Conference, 2026)
This contribution argues that to make our television histories properly “useful” – informative and transformative for a range of stakeholders including scholars, students, citizens, and working people – we must embrace a radically expansive understanding of what and where television is (and has been). To this end, I explore the challenges facing the historical preservation and research of “taste-less” TV: television situated beyond the cultural hierarchies that commonly animate analytical frameworks linked to the small screen. Instead of public service broadcasting, news, and entertainment, this presentation will focus on archiving “useful television.” Adapting Charles R. Acland and Haidee Wasson’s term (2011, 3) describing cinema deployed “to satisfy organizational demands and objectives, that is, to do something in particular,” I will consider a range of televisual applications too often forgotten in historical accounts of the so-called domestic medium: CCTV surveillance, workplace training videos, telemetry, classroom broadcasts, therapeutic self-evaluation, military research, and business satellite channels, among others. Given its frequent confinement to institutional spaces, I will likewise suggest useful television is often local television – not only in terms of its signal reach, but also in its attempts to serve bounded and bonded communities, manage local action, and construct geographical imaginaries. Ultimately, I will argue that the challenges that come with unlocking the archives of useful television (restricted or closed archival collections, unrecorded applications, institutional budget cuts, record scarcity, vanishing ephemera, and scale) represent intensified versions of the problems facing commercial and public service television archives. Furthermore, confronting these tensions through archival strategies that include developing digital collections and tools, building communities of inquiry, and engaging theories and practices of archival appraisal supports researchers working along the entire continuum of television’s study. Finally, I push these correspondences beyond shared difficulties to encompass a unified, if heterogenous, scholarly project invested in television’s relationship to culture, power, identity, art, and everyday life. Doing so both clarifies and deepens the stakes of televisual study and preservation.